2021
DOI: 10.3390/cancers13174346
|View full text |Cite
|
Sign up to set email alerts
|

Radium-223 Treatment of Patients with Metastatic Castration Resistant Prostate Cancer: Biomarkers for Stratification and Response Evaluation

Abstract: Radium-223 dichloride ([223Ra]RaCl2; Ra-223) is a targeted alpha-emitting radiopharmaceutical which results in an overall survival and health related quality of life (HRQoL) benefit in symptomatic patients with metastatic castration resistant prostate cancer (mCRPC) and predominantly bone metastasis. Although effective, options to select patients who will derive treatment benefit and to monitor and predict treatment outcomes are limited. PSA response and radiographic evaluation are commonly used in mCRPC treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…A growing body of literature suggests that the efficacy of Radium-223 is closely dependent on pre-treatment 'risk stratification [ 14 ]. Therefore, several studies investigated many potential baseline prognostic factors, whose application might optimize the patient's selection process [ 34 ]. Coherently with the existing literature, in the present study we observed a prognostic role of baseline PSA, ALP, LDH, and haemoglobin in a cohort of mCRPC candidates to receive Radium-223 [ 35 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that the efficacy of Radium-223 is closely dependent on pre-treatment 'risk stratification [ 14 ]. Therefore, several studies investigated many potential baseline prognostic factors, whose application might optimize the patient's selection process [ 34 ]. Coherently with the existing literature, in the present study we observed a prognostic role of baseline PSA, ALP, LDH, and haemoglobin in a cohort of mCRPC candidates to receive Radium-223 [ 35 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…57,58 This mechanism works by using exogenous radium-223 which is chemically related to calcium and is deposited by activated osteoblasts adjacent to cancer cells. 59,60 This proximity results in selective cytotoxicity to cancer cells. This allows the delivery of high-energy radiation to bone metastases while minimizing toxicity to other cells within the bone microenvironment.…”
Section: Prevalent Lesions In Humans Xenograft Modelsmentioning
confidence: 99%
“…The 223 Ra acts as a calcium mimetic drug, predominantly accumulating in the bone tissues of the body [ 48 , 49 ]. In fact, 223 Ra is currently used in targeted alpha therapy (TAT) for treating bone metastases of patients with metastatic castration-resistant prostate cancer [ 50 ]. For this, 223 Ra is used in the chemical form of the salt radium dichloride ([ 223 Ra]RaCl 2 ).…”
Section: Introductionmentioning
confidence: 99%